The humour of Italy - Werner, Alice, 1859-1935; Faldi, Arturo, 1856-1911 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Humour of Italy" by Alice Werner and Arturo Faldi is a collection of humorous anecdotes and tales derived from Italian literature, written in the late 19th century. It compiles various stories and works, reflecting the wit and light-heartedness found within the cultural fabric of Italy through the ages, from poets like Dante to comic characters like Calandrino. This anthology aims to showcase the unique aspects of Italian humor and its evolution, presenting a rich tapestry of comedic narratives intertwined with cultural observations. At the start of the collection, the introduction sets the stage by discussing the nature of Italian humor, which ranges from broad farce to subtle drollery. The anecdotes exemplify this blend, offering stories like that of Calandrino, a simple painter who is easily fooled by his friends into a comical search for imaginary stones, and a clever miller who outsmarts a cruel lord. We also encounter the likes of Dante, who humorously reprimands a blacksmith for misinterpreting his poetry. These early selections present a thematic exploration of folly, social critique, and the context of humor within daily life, illustrating the liveliness and depth of Italian comedic tradition. (This is an automatically generated summary.)
Release date is 2023-09-23
Richard Tonsing, MFR, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Italian wit and humor